2003
DOI: 10.1023/a:1025650914947
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Gamma-aminobutyrate (GABA) is a ubiquitous four-carbon, non-protein amino acid synthesized by glutamate decarboxylase. Previous research suggests that the endogenous synthesis of GABA, a naturally occurring inhibitory neurotransmitter at neuromuscular junctions, serves as a plant resistance mechanism against invertebrate pests. In this study, two homozygous transgenic tobacco lines constitutively overexpressing a single copy of a full-length chimeric glutamate decarboxylase cDNA and possessing enhanced capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…The GABA-induced degradation of OC8-HSL would, however, constitute part of the plant defense mechanisms against bacterial infection. Such a role has already been assigned to GABA during infestation or feeding by invertebrate pests, whose neuromuscular junctions are very sensitive to GABA (21,24). The transgenic GAD and GAD⌬C tobacco lines used in this work were previously described as more resistant than wild-type tobacco to infestation by the northern root-knot nematode (21).…”
Section: Discussionmentioning
confidence: 89%
“…The GABA-induced degradation of OC8-HSL would, however, constitute part of the plant defense mechanisms against bacterial infection. Such a role has already been assigned to GABA during infestation or feeding by invertebrate pests, whose neuromuscular junctions are very sensitive to GABA (21,24). The transgenic GAD and GAD⌬C tobacco lines used in this work were previously described as more resistant than wild-type tobacco to infestation by the northern root-knot nematode (21).…”
Section: Discussionmentioning
confidence: 89%
“…This mutant has not been used and characterized in the context of herbivory. Previous studies observed that increased concentrations of GABA can affect insect’s development (Ramputh and Bown, 1996; MacGregor et al, 2003; Bown et al, 2006; Scholz et al, 2015). We used the pop2-5 mutant to further evaluate the effect of high endogenous GABA concentration in planta on the herbivorous larvae of Spodoptera littoralis in a feeding assay ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 98%
“…Due to the finding that higher GABA levels can affect insects (Ramputh and Bown, 1996 ; MacGregor et al, 2003 ; Bown et al, 2006 ) the influence of different endogenous GABA concentration in planta was investigated in parallel in an insect herbivore feeding assay. In contrast to former experiments (MacGregor et al, 2003 ; Bown et al, 2006 ), we did not look for feeding preferences but for insect performance on different mutant lines. Therefore, we carried out a bio-assay employing the three plant lines, wild type, g ad1/2 , and g ad1/2 x pop2-5 plants (Figure S4 ), and herbivorous larvae of the generalist lepidopteran species Spodoptera littoralis .…”
Section: Resultsmentioning
confidence: 99%
“…(ii) Leaf tissues of soybean ( Glycine max ) and tobacco ( Nicotiana tabacum ) that were only slightly wounded by crawling insect species ( C. rosaceana and the tobacco budworm, Heliothis virescens , respectively) showed a GABA accumulation up to 4- to 12-fold within 5–10 min (Bown et al, 2002 ). (iii) Transgenic N. tabacum plants with elevated GABA levels due to constitutive transgenic expression of a GAD enzyme were more resistant to both H. virescens larvae and Meloidogyne hapla , the root-knot nematode (MacGregor et al, 2003 ; McLean et al, 2003 ; Bown et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%